Beyond Bilas: The Enga Take Anda1. Issue 3 (20th October 2013) - Wiessner, Polly; Tumu, Akii
Abstract A crucial issue facing anthropologists, linguists, and museums today is what to do with research material and artifacts that have accumulated over the years. In 2005 we sought ways to return 20 years of material on Enga history and tradition to the people of Enga Province at a time when rapid change was leaving young generations with little sense of their cultural heritage. The goal was to build a center, the Enga Take Anda, House of Traditional Knowledge, that would provide knowledge of the past to help Enga understand recent changes and to consider what should be carried forward and what left behind. To be effective, the Enga Take Anda would have to be a museum and as well as a resource center with an active role in Enga schools and the Village Court system. We describe here challenges and successes in this endeavor. The establishment of the Take Anda has involved much trial, error, flexibility and persistence, largely persistence.